A comprehensive method to generating and identifying transgenic tobacco lines with a single transgene integration locus for functional analysis - Hilman, Mohamad Shafek; Nawawi, Omar; Azhari, Mohd Farhan; Bai, Tianqi; Zhang, Cuixian; Abdullah, Mohd Puad; Masani, Mat Yunus Abdul; Yusuf, Chong Yu Lok (Universiti Putra Malaysia, 2025)
Tobacco is a popular model plant used for studying gene function. The generation of transgenic tobacco is tremendously essential in functional genomics. The generated transgenic plants must undergo careful selection and analysis before being used. However, most published protocols for generating transgenic tobacco for functional genomics are not comprehensive and involve sophisticated equipment. This study demonstrates an efficient and comprehensive method for developing and selecting transgenic tobacco lines without involving sophisticated equipment. Transgene was delivered into the genome of a tobacco plant via Agrobacterium tumefaciens. Polymerase Chain Reaction (PCR) was performed to verify the integration of transgenes in the putative primary transformants. Reverse Transcription-Polymerase Chain Reaction (RT-PCR) examined transgene expressions. The number of transgene integration loci (TIL) was determined by transgene segregation analysis. PCR results revealed that ≈97% of the primary transformants were positive. The transgene was highly expressed in the transgenic plants. Segregation analysis showed that 47.6%–66.7% of the transgenic plants contained a single TIL, and the T1 and T2 progenies inherited the transgene. Homozygous transgenic lines with a single TIL were successfully developed by using our method. This manuscript encompasses detailed guidance on genetic transformation, molecular analysis, seed production, and transgene segregation analysis. It serves as a guideline for the researchers to produce transgenic tobacco lines that can be used for functional analysis. The procedures described here can be conducted in standard laboratories as they require no high-end equipment. This comprehensive and efficient method for generating transgenic tobacco will foster functional genomics.